Francis of Assisi on Protecting, Obeying, and Worshiping with Animals. (2nd October 2021) - Crane, Susan
ABSTRACT: Francis of Assisi is well known for his devotion to all God's "creatures, " from worms and fish to moon and stars. Francis's devotion also has some little known dimensions that are unprecedented in his own time but that anticipate central tenets of posthumanist animal theory and ecotheology. In the earliest Franciscan documents, Francis asserted that he obeyed non-human animals as an expression of faith. He worshiped with them, protected their lives, and conflated their material welfare with their symbolic meanings. These aberrant features of Francis's piety were suppressed soon after his death, but they merit close attention for the ways in which they anticipate contemporary theorists' efforts to de-center the human, recognize animal participation in human cultures, and envision a coherently material and spiritual theology.